Organizations, Participation and Recession: An Analysis of Recent Evidence - Long, Richard; Warner, Malcolm (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1987)
This paper examines the changing pattern of worker participation in organizations during recent conditions of economic down-turn. The authors conclude that the current recession has served as a catalyst to force many organizations and their members to recognize that traditional management approaches and resulting employee responses have become increasingly inadequate in the light of wider social changes, and that there is more support for an «evolutionary ratchet» as opposed to a «cyclical» notion of participation.